Beef as a source of multi-resistant Escherichia coli O157 harbouring transferable plasmid and resistance phenotype - Son, Radu; Sahilah, A.M.; Gulam, R.; Raha, A .R.; Rozila, A.; Samuel, L. (1998)
Sixty five strains of enterohaemorrhagic Escherichia coli (EHEC) 0157 isolated frorq frozen imported beef, were examined for presence of plasmid DNA and their susceptibility to seventeen antimicrobial agents. Forty isolates were found to contain plasmid DNA ranging in sizes from 1.38 to 86 megadaltons. All were susceptible to cephalosporin, cepoferazone, kanamycin and nalidixic acid. but multiple resistance to at least four of the antibiotics tested was observed with resistance to bacitracin (100%), methicillin (100%), vancomycin (100%), clindamycin (97%) and novobiocin (92%) most common. In two of the selected multiply-resistant and plasmid containing isolates, resistance was associated with carriage of a 6O megadalton plasmid (EC 1.21) and 1.8, 3, 3.9, 5.1 and 60 megadaltons (EC1.38) plasmids, which were transmissible to the Escherichia coli K12 recipient. It is concluded that imported frozen beef form a reservoir of R plasmid carrying Escherichia coli O157 in the study area.